2015
DOI: 10.1128/aem.00958-15
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Dilution Procedure Used To Manipulate Microbial Biodiversity in Terrestrial Systems

Abstract: bIt is hard to assess experimentally the importance of microbial diversity in soil for the functioning of terrestrial ecosystems. An approach that is often used to make such assessment is the so-called dilution method. This method is based on the assumption that the biodiversity of the microbial community is reduced after dilution of a soil suspension and that the reduced diversity persists after incubation of more or less diluted inocula in soil. However, little is known about how the communities develop in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 40 publications
7
58
0
Order By: Relevance
“…Our results confirm the statement of Yan et al . () that the dilution method is effective in obtaining a decreasing gradient in microbial OTUs richness, but that it allows no accurate predictions on the community structure and genera abundances. Soil bacterial richness has been shown to be of poor importance for mechanisms such as degradation of carbon sources or nitrogen cycling, since bacterial species are probably redundant in ecosystem functioning (see Roger et al ., for an overview of the bacterial diversity‐ecosystem functioning literature including the dilution approach).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the statement of Yan et al . () that the dilution method is effective in obtaining a decreasing gradient in microbial OTUs richness, but that it allows no accurate predictions on the community structure and genera abundances. Soil bacterial richness has been shown to be of poor importance for mechanisms such as degradation of carbon sources or nitrogen cycling, since bacterial species are probably redundant in ecosystem functioning (see Roger et al ., for an overview of the bacterial diversity‐ecosystem functioning literature including the dilution approach).…”
Section: Discussionmentioning
confidence: 99%
“…The one exception, Valentin et al 26 , found a positive relationship, but in that study, field-collected microbial communities were serially diluted and re-inoculated into laboratory wood incubations. Serial dilution does not necessarily remove microbial species, but it does make all species less abundant 27 , which might have reduced decomposition rates. In contrast, field studies to date have reported only ambiguous relationships between fungal diversity and decomposition rates.…”
Section: Discussionmentioning
confidence: 99%
“…which is expected given that dilution alone reduces diversity (Franklin et al, 2001, Hewson et al, 2003 Schaffer et al, 2000, Yan et al, 2015). Comparing the diversity values obtained after one day of 400 treatment (we were not able to compare diversity values at 10 days of treatment due to the low read 401 number in the 10-day no alkane control), and the 10 day cultures, indicated that exposure to gasoline and 402 n-hexane reduced diversity to a greater degree than seen in the dodecane treatment or the no alkane 403 further study would be required to determine if the sediment microbial community of the fringing marsh 410…”
mentioning
confidence: 88%